2015
DOI: 10.1007/s11255-015-0954-8
|View full text |Cite
|
Sign up to set email alerts
|

Augmenter of liver regeneration attenuates inflammation of renal ischemia/reperfusion injury through the NF-kappa B pathway in rats

Abstract: ALR can improve renal function and inhibit the expression of inflammatory factors. This protects against renal ischemia reperfusion injury, which may be associated with preventing NF-κB activation in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…We also observed tubular epithelial necrosis by microscopic detection, similar to other studies on AKI caused by different reasons [3133]. Applied HS, less necrotic tubules were found with a lower tubular damage score, which suggests a relief of early AKI post burn.…”
Section: Discussionsupporting
confidence: 89%
“…We also observed tubular epithelial necrosis by microscopic detection, similar to other studies on AKI caused by different reasons [3133]. Applied HS, less necrotic tubules were found with a lower tubular damage score, which suggests a relief of early AKI post burn.…”
Section: Discussionsupporting
confidence: 89%
“…Nuclear factor-kappa B (NF-κB), a transcription factor, has complex roles in renal functions as well as in cell cycle changes when cellular stress was provoked, ROS was produced and DNA damage occurred [18]. NF-κB is involved in the genesis of several inflammatory diseases including RI/RI [18].…”
Section: Introductionmentioning
confidence: 99%
“…NF-κB is involved in the genesis of several inflammatory diseases including RI/RI [18]. The activation of NF-κB is extremely important for both oxidative stress and inflammatory signaling pathways in RI/RI.…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory reactions can markedly promote IRI (10). Certain reports have suggested that IRI is a process of inflammation, although this is debated, and reflects the importance of IRI in inflammatory reactions (11). A cascade network, comprising reactive oxygen species, a substantial number of NO generated by inducible nitric oxide synthase (iNOS) and inflammatory reactions is an important mechanism of IRI (12).…”
Section: Introductionmentioning
confidence: 99%